Body dissatisfaction and body weight status perception among overweight and obese children - Abdul Karim, Wan Mohd Nurussabah; Saad, Hazizi Abu (International Journal of Public Health Science (IJPHS), 2025)
Children's perceptions of their weight, body image, and misjudgment of their actual body size can lead to body dissatisfaction, increasing health concerns related to childhood obesity. This cross-sectional study investigated the associations between body dissatisfaction and body weight status (BWS) perception among overweight and obese children aged 10 and 11 years. A total of 398 overweight and obese participants were selected and recruited from eleven primary schools in the state of Kedah, Malaysia. The questionnaire on body image perception was adapted from ‘The seven male and female child figure rating scale,’ and information on BWS perception was collected through a question on how respondents perceived their current BWS. The majority of children (89.4%) desired a smaller body size, and 55.5% did not perceive their BWS correctly; 50% were categorized as “underestimators,” and 5.5% as “overestimators.” There was no significant association between body size discrepancy score and age (p=0.110). However, a significant association was found between the perception of current body image and body mass index (BMI) (p<0.001). The high discrepancies between the perception of current body image and actual weight status need to be addressed, as this misperception could hinder overweight and obese children from successfully achieving a healthy body weight.